Siti Norkiah Mahmud : srikandi dari Pahang Utara - Mohamed Salleh Lamry (Petaling Jaya, Selangor : Strategic Information and Research Development Centre, 2011)
Biography of Siti Norkiah Mahmud, a Malay revolutionist fighting against British colonial in Malaysia and a wife of the leader of Malayan Communist Party.
Keywords: Siti Norkiah Mahmud, -- 1920-; Malayan Communist Party -- History; Revolutionaries -- Malaysia -- Biography; Communists -- Malaysia -- Biography